2018
DOI: 10.1007/s00330-018-5389-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics of high-grade serous ovarian cancer: association between quantitative CT features, residual tumour and disease progression within 12 months

Abstract: • No residual tumour (RT) at surgery is the most important prognostic factor in OC. • Radiomic features related to mass size, randomness and homogeneity were associated with RT. • Progression of disease within 12 months (PD12) indicates worse prognosis in OC. • A model including clinical and radiomic features performed better than only-clinical model to predict PD12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 29 publications
3
55
0
1
Order By: Relevance
“…Radiomics mainly improves the prediction performance of medical images by improving medical image analysis and using computer algorithms to extract thousands of quantitative features (19). Although these characteristics can reflect tumor biology behavior from various aspects (33), the correlation is also difficult to comprehend between single radiomics features and biological behaviors. Moreover, constructing multi-feature panels is a more common evaluation method (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics mainly improves the prediction performance of medical images by improving medical image analysis and using computer algorithms to extract thousands of quantitative features (19). Although these characteristics can reflect tumor biology behavior from various aspects (33), the correlation is also difficult to comprehend between single radiomics features and biological behaviors. Moreover, constructing multi-feature panels is a more common evaluation method (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies, thus far, have applied radiomics in patients with ovarian cancer, mainly evaluating the ability of texture features to characterize tumor tissue [15,17,39,40] and predict outcome [14,15,17,18,21,22,39]. Best to our knowledge, Table 4 Associations between protein abundance and CT-based imaging traits previously found to be prognostic in patients with HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that MRI-derived radiomic features can discriminate between benign and malignant ovarian masses, with a high accuracy of 87% [12]. Furthermore, CT radiomic features of patients with ovarian cancer correlate with response to therapy [13], progression-free survival [14,15], and overall survival [15], and can identify patients at higher risk for recurrence [16]. Recent work by our group focused on evaluating the possible associations between CT imaging traits and texture metrics with genomics data and patient outcome [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown, for example, dissimilarities in texture metrics between implants to be associated with poorer prognosis. Moving forward, the combination of radiomic features and clinical data may allow the creation of predictive models of resectability or of tumour progression [5]. However, before radiomics is integrated as a clinical adjunct, some hurdles (reproducibility, lack of automation,…) have to be overcome.…”
Section: Current Research and Perspectivesmentioning
confidence: 99%